FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN BANK RAKYAT INDONESIA (BRI) CABANG PALANGKA RAYA - Robert Fransiska (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
The research aims to examine and analyze the influence of leadership style,motivation and work discipline toward performance of employee in Lion GroupDistric Kalimantan. Data collected through distribution of questionnaires and it isimplemented to BRI Distric Palangka Raya 112 employee. Analysis of data in thisresearch using the help of SPSS version 27. A sampling technique uses a censusmethod and data test technique is used within the research includes validity test byfactor analysis, reliability test with cronbach. Classic assumption test and doublelinear regression analysis, to verify and to prove the research hypothesis.Analysis result demonstrates that leadership style have a positive influencetoward employee performance. Motivation have a positive influence toward employeeperformance and work discipline have a positive influence toward employeeperformance.